EVALUASI PENERAPAN ISO 9001:2015 PADA PT PULAU SAMBU GROUP (PSG) SUNGAI GUNTUNG KABUPATAN INDRA GIRI HILIR RIAU - Denny Handayani (Manajemen Bisnis, 2018)
PT Pulau Sambu Guntung was a company engaged in the plantation sector, industry and trade, companies that process raw materials into a cream of coconut and palm oil producing strain.In the supply of raw materials, the company acquired by purchase from the supplier, and the company has a coconut plantation which is only taken 10% of the plantation area.Because it will be exported to Europe then came the problem because in Europe the standard is set too high, the ISO shall not be granted and must make improvements.This study aimed to analyze the application and the requirements of the quality management system ISO 9001: 2015.The analysis tool used is descriptive analysis.The results showed that the clause was appropriate and meet the target, but there is a clause that is appropriate but not running optimally.Therefore still needs to be improved continuously in order to run optimally.